Ballerina becky: ladybird - Ross, Mandy (Ladybird London, 2004)
Ballerina Becky is practising for the Story Town Ballet. Her fairy tutu and wings have arrived and everyone is excited. But what if Ballerina Becky feels a bit wobbly on stage?